Panelist Number 1 - Folts, Franklin (Academy of Management Journal, 1958)
Provides information on a middle management program at Harvard University in Cambridge, Massachusetts. Characteristics of participants in middle management program; Knowledge, attitudes and skills possess by men when they come to Harvard.